ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM - Bunga Nur Islamiyah; Wijayanti, Anita; Masitoh W, Endang (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The research aims to test and find out whether there is an effect of DPS, EPS, LDR, and NPM on stock prices in Banking companies in 2014-2018. The object of this research is a banking company listed on the Indonesia Stock Exchange in 2014-2018, totaling 43 companies. The technique used is purposive sampling. The samples used in this study were 10 Perbakan companies listed on the IDX. This research uses Multiple Linear Regression Analysis method. The results of this study indicate that the Dividend Per Share (DPS) and Earning Per Share (EPS) affect the stock prices of banking companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018. While the Loan to Deposit Ratio (LDR) and Net Profit Margin (NPM) have no effect on the stock price of banking companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018.